Knowledge-based expectation effects on pitch perception: A cross-cultural investigation - Kaplan, Elif Canseza. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
Earlier studies have shown that harmonic (Bigand & Pineau, 1997) as well as tonal expectations (Marmel, Perrin, & Tillmann, 2011; Marmel, Tillmann, & Dowling, 2008) influence pitch processing. The ending of a melody fragment either with full or half/suspended-cadence affects the sensitivity towards pitch deviations. In the current study we investigated the influence of such knowledge-based expectations in Turkish makam music, which is a musical system that includes more minute pitch intervals than Western music. We showed that despite the narrower pitch intervals of makam music, both Western tonal (Exp. 1A) and Turkish makam (Exp. 1B) contexts influence processing of pitch in a similar fashion. In addition, a second control experiment (Exp. 2) that measured psychophysical sensitivity thresholds of pitch deviations confirmed that the effect we observed in Exp. 1 was not due to the participants’ inability to hear pitch deviations.
Keywords: Melody.; Sound-waves.; Musical pitch.